2006
DOI: 10.1074/jbc.m505822200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of HSF1 by MAPK-Activated Protein Kinase 2 on Serine 121, Inhibits Transcriptional Activity and Promotes HSP90 Binding

Abstract: Heat shock transcription factor 1 (HSF1) monitors the structural integrity of intracellular proteins and its regulation is essential for the health and longevity of eukaryotic organisms. HSF1 also plays a role in the acute inflammatory response in the negative regulation of cytokine gene transcription. Here we show, for the first time, that HSF1 is regulated by the proinflammatory protein kinase MAPKAP kinase 2 (MK2). We have shown that MK2 directly phosphorylates HSF1 and inhibits activity by decreasing its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 57 publications
3
76
0
1
Order By: Relevance
“…HSF1 may also participate in the progression of gastrointestinal cancers by repressing the promoter of the XAF1 gene. XAF1 is a suppressor of XIAP, a caspase 3 inhibitory protein and loss of XAF1 thus leads to protection from caspase-dependent apoptosis (Wang et al, 2006). Elevation of HSF1 during malignant transformation may thus be implicated in tumorigenesis through multiple mechanisms, including expression of antiapoptotic proteins HSP70 and XIAP and repression of ERE-regulated genes including pro-apoptotic c-Myc (Wang et al, 2004b;Khaleque et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…HSF1 may also participate in the progression of gastrointestinal cancers by repressing the promoter of the XAF1 gene. XAF1 is a suppressor of XIAP, a caspase 3 inhibitory protein and loss of XAF1 thus leads to protection from caspase-dependent apoptosis (Wang et al, 2006). Elevation of HSF1 during malignant transformation may thus be implicated in tumorigenesis through multiple mechanisms, including expression of antiapoptotic proteins HSP70 and XIAP and repression of ERE-regulated genes including pro-apoptotic c-Myc (Wang et al, 2004b;Khaleque et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously found that Cdc37 directly interacts with HSF1. 1 Cdc37 may therefore participate in the release of HSF1 from HSP90 complexes, an essential step in HSF1 activation (40). Loss of HSP70 induction may contribute to the increased 17AAG-induced killing in Cdc37-depleted cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…19 Several heat shock proteins, including hsp 27, hsp 70, and hsp 90, have been found to inhibit NF-B activation. [61][62][63] Besides, many compounds that activate the heat shock response also inhibit NF-B. 64 Thus, it is possible that heat shock protein is involved in suppression of TNF-induced NF-B activation by celastrol.…”
Section: Discussionmentioning
confidence: 99%